OP0163 Evaluation of Influenza and Pneumococcal Vaccine Responses in Rheumatoid Arthritis Patients Using Tofacitinib. (23rd January 2014) - Winthrop, K. L.; Neal, J.; Hrycaj, P.; Soma, K.; Wilkinson, B.; Hodge, J.; Zwillich, S. H.; Wang, T.; Rottinghaus, S.; Kawabata, T.; Riese, R.; Mebus, C.; et al.
Abstract : Background: Tofacitinib (CP-690, 550) is a novel, oral Janus kinase inhibitor for the treatment of rheumatoid arthritis (RA). Objectives: To evaluate effects of tofacitinib alone, and in combination with methotrexate (MTX), on immunogenicity of influenza and pneumococcal polysaccharide vaccines (NCT01359150 ). Methods: Patients (pts) with RA were randomised 1:1 to receive tofacitinib 10 mg BID or placebo (PBO), stratified by background MTX. All pts were vaccinated with the 2011-2012 trivalent influenza vaccine (constituents: A/California/7/2009 (H1N1); A/Perth/16/2009 [H3N2]; B/Brisbane/60/2008) and PNEUMOVAX-23 ® (PPV23, Merck & Co., Inc) pneumococcal vaccine 28 days post-drug initiation. Pneumococcal antibody (Ab) concentrations and influenza Ab titres were measured at vaccination and 35 days post-vaccination. Primary endpoint: proportion of pts achieving a satisfactory humoral response at 35 days post-vaccination to (a) pneumococcal vaccine (≥2-fold increase in Ab concentrations against ≥6 of 12 pneumococcal antigens [Ag]) and (b) influenza vaccine (≥4-fold increase in Ab titres against ≥2 of 3 influenza Ag). Secondary endpoints included proportion of pts achieving protective influenza hemagglutination (HI) titres ( ≥ 1:40 influenza Ab titre in ≥2 of 3 Ag), and fold increase of serotype-specific anti-influenza and anti-pneumococcal Ab levels. Results: 214 of 223 randomised pts were vaccinated. Immunogenicity evaluations and analyses were performed in 200 pts (tofacitinib, N=102; PBO, N=98, approximately half of each group received MTX). At 35 days post-vaccination, similar proportions of pts developed satisfactory humoral responses to influenza vaccine in the two groups; fewer tofacitinib-treated pts achieved a satisfactory humoral response to PPV23 vaccine, particularly in pts with background MTX (Table 1 ). The proportion of pts achieving protective influenza HI titre was lower with tofacitinib (76.5%) vs PBO (91.8%). Post-vaccination pneumococcal Ag and influenza serotype-specific geometric mean fold rise (GMFRs) were lower in pts receiving tofacitinib vs PBO. Conclusions: Similar proportions of RA pts receiving tofacitinib 10 mg BID vs PBO achieved adequate influenza vaccine humoral responses with or without MTX. PPV23 immunogenicity was decreased in pts receiving tofacitinib vs PBO, particularly in those also receiving MTX. To maximise vaccine response, PPV23 should be given prior to MTX or tofacitinib initiation, as per general recommendations for patients with RA. Disclosure of Interest: K. Winthrop Grant/research support from: Oxford Immunotech; Pfizer Inc., Consulting fees or other remuneration: Abbott; Pfizer Inc; UCB; Amgen; Cellestis, J. Neal Grant/research support from: Pfizer Inc., Consultant for: Pfizer Inc., P. Hrycaj Grant/research support from: Pfizer Inc., Consultant for: Pfizer Inc., K. Soma Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., B. Wilkinson Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., J. Hodge Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., S. Zwillich Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., T. Wang Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., S. Rottinghaus Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., T. Kawabata Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., R. Riese Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., C. Mebus Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., J. Bradley Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., C. Bingham III Grant/research support from: BMS, Janssen/J&J, Genentech/Roche, UCB, Consultant for: Pfizer Inc., Abbott, Amgen, BMS, Celgene, Genentech/Roche, Janssen/J&J, UCB